Healthcare cybersecurity and cybercrime supply chain risk management - Dr. Jorja Wright (Health Economics and Management Review)
Cybersecurity is paramount in today’s rapidly evolving healthcare industry, particularly as supply chain management and logistics undergo digital transformation. This study examines the substantial threat posed by cybercrime to patient safety, data security, and operational efficiency within healthcare logistics and supply chain management. These risks can significantly impact an organization’s reputation and financial stability, necessitating vigilant detection and mitigation efforts by healthcare companies. As the primary defence against online threats, cybersecurity plays a pivotal role in preventing data breaches, cyberattacks, and other malicious activities that could have devastating consequences for the healthcare sector. Its core objective is to ensure the availability, confidentiality, and integrity of data, systems, and resources within the realm of healthcare supply chain management and logistics. Patient data protection stands out as a critical aspect of cybersecurity in this context. Healthcare logistics and supply chain management systems frequently handle sensitive patient data, encompassing billing details and medical histories. The compromise of such data places patient trust and the organization’s regulatory compliance at risk, potentially leading to identity theft, fraudulent claims, and privacy breaches. Furthermore, safeguarding the security of medical equipment is of paramount importance. With the increasing connectivity of these devices through the Internet of Things (IoT), they become more vulnerable to cyberattacks. Apart from jeopardizing patient safety, a breach in medical device security raises questions about the authenticity and reliability of healthcare products and services. Another pressing issue that healthcare institutions must address is unauthorised access to their systems. Cybercriminals persistently seek entry points into these systems to exploit vulnerabilities for illicit or profitable purposes. Robust cybersecurity measures are essential to thwarting unauthorised access and ensuring that only authorised individuals can access and modify sensitive medical data. Maintaining the accuracy of patient records is crucial for efficient supply chain management and healthcare logistics. Cyberattacks that manipulate or corrupt patient records can lead to medical errors, endangering patient safety. Consequently, cybersecurity measures must include safeguards to preserve the integrity and accuracy of these records. Beyond these immediate concerns, cybersecurity is instrumental in preventing disruptions to healthcare operations and services. Downtime resulting from cyberattacks can be catastrophic, impeding patient care and undermining the overall effectiveness of supply chain management and healthcare logistics. Cybersecurity safeguards continuous healthcare services by guaranteeing the security and accessibility of data and systems. Furthermore, cybersecurity plays a pivotal role in protecting the integrity, trust, and reputation of healthcare organizations. A cyberattack or data breach can tarnish an organization’s reputation and erode patient confidence. Such damage can have enduring repercussions, affecting an organization’s ability to attract clients, partners, and investors.